How the Military Invasion in Ukraine Led to the Restriction on the Political Rights of the Citizens of the Russian Federation? - Boyuklieva, Iliana (Law Journal of New Bulgarian University, 2023)
The Russian invasion of Ukraine since February 2022 has shaken up the peace in the world and it has dire international and economic consequences, but it also pushes the Russian Federation to a series of restrictions on the political rights of Russian citizens. The participation of Russian citizens in social and political life is hindered by the repressive measures to the extent that the Constitution is nothing more than a hollow facade, behind which unfolds arbitrariness, totalitarianism, and destruction of individual freedom.